2022
DOI: 10.1002/mco2.120
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphatase SHP2 exacerbates psoriasis‐like skin inflammation in mice via ERK5‐dependent NETosis

Abstract: Psoriasis is a chronic inflammatory skin disease, often accompanied by increased infiltration of immune cells, especially neutrophils. However, the detailed mechanism of the neutrophil function in psoriasis progression remains unclear. Here, we found that both Src homology‐2 domain‐containing protein tyrosine phosphatase‐2 (SHP2) and neutrophils were highly correlated to developing psoriasis by single‐cell ribonucleic acid (RNA) sequencing and experiment verification. The deficiency of SHP2 in neutrophils sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“… 92 We also recently found that SHP2 in neutrophils aggravated psoriasis by promoting the formation of extracellular neutrophil traps and the subsequent cell death known as NETosis via the ERK5 pathway. 93 SHP2 also mediated keratinocyte proliferation, migration, and differentiation through ERK activation in an IL-22-mediated psoriasis-like model. 94 These results indicated that the function of SHP2 in psoriasis varied depending on the specific immune cell type.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 90%
“… 92 We also recently found that SHP2 in neutrophils aggravated psoriasis by promoting the formation of extracellular neutrophil traps and the subsequent cell death known as NETosis via the ERK5 pathway. 93 SHP2 also mediated keratinocyte proliferation, migration, and differentiation through ERK activation in an IL-22-mediated psoriasis-like model. 94 These results indicated that the function of SHP2 in psoriasis varied depending on the specific immune cell type.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 90%
“…Blocking PAD-4 was found to disrupt network formation and therefore increase the risk of bacterial infection in animals [ 26 ]. In addition, the study of Ding et al (2022) showed remarkably ameliorated psoriasis-like symptoms in PAD-4 knockout mice [ 44 ]. Thus, studies using knock-out animals indicated the participation of PAD-4 as a required component for NET-dependent innate antimicrobial immunity [ 26 ] as well as a factor firmly associated with psoriasis development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study of Ding et al (2022) showed remarkably ameliorated psoriasis-like symptoms in PAD-4 knockout mice [ 44 ]. Thus, studies using knock-out animals indicated the participation of PAD-4 as a required component for NET-dependent innate antimicrobial immunity [ 26 ] as well as a factor firmly associated with psoriasis development [ 44 ]. Additionally, PAD-4 has been shown to participate in the regulation of proliferation and hematopoiesis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Src homology 2 (SH2) domain-containing protein tyrosine phosphatase 2 (SHP2) is a non-receptor protein tyrosine phosphatase (PTP) encoded by the PTPN11 gene [ 1 , 2 , 3 , 4 , 5 ]. The SHP2 structure contains two tandem SH2 domains (N-SH2 and C-SH2), a PTP catalytic domain and a C-terminal tail with two tyrosine phosphorylation sites [ 6 , 7 , 8 , 9 ]. SHP2 is located in the cytoplasm, can be recruited by receptor tyrosine kinases (RTKs) to induce cell signaling and participates in the intracellular oncogenic RAS/MAPK cell signaling cascade [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%